THE PROBLEMS OF INDONESIAN MIGRANT WORKERS' RIGHTS PROTECTION IN MALAYSIA - Sri Wahyono (Jurnal Kependudukan Indonesia, 2007)
This paper describes the poor state of protection of Indonesian Migrant Workers Rights in almost all economic sectors, both formal and non-formal, in Malaysia. In this research, most of the randomly interviewed respondents were Indonesian Migrant Workers (TKI) with a few Philipinos, Indians and Vietnamese employed in various sectors such as domestic work, manufacturing, plantations, construction, or retail (stores and cafes). Many of the TKI living and working in Malaysia did not receive their full rights as workers and sometimes even lost their basic rights such as that to_a minimum wage, not being not having their wages withheld or not paid at all their withhelds, as well as a refusal to have their passports returned. Many of the Indonesian workers were physically and sexually abused by their employers. For example, some Indonesian workers employed in the plantation and construction sectors had to stay in very poor accommodation while many female workers were victimized into becoming forced prostitutes by their sponsors. In addition, some of the TKI had to face serious problems of protection; many as vic~ of corrupt practices such as the imposition of illegal levies by Malaysian olice and immigration staffs suffered by the TKI were demands for payments; extortion of money and confiscation of valuables factors contributing to the vulnerability of Indonesian migrant workers such as: a) Low formal education and lack of relevant training; b )Lack of information on how to obtain travel documents, how to apply for jobs or visas and how much to pay in fees; c) Lack of knowledge or understanding of the labour law and immigration regulations of Malaysia as the receiving country; d) Falsifying ofiD Cards, data of passports and other travel documents in the recruitment and deployment process by recruiting agents and involving immigration officials.Keywords: Indonesian migrant workers, Malaysia